Optimalisasi Strategi Pemasaran Berbasis Utilitarian Value dan Digital Marketing di Kampung Gambut Siantan Hilir - Theodora, Cindy; Wendy, Wendy; Meisa, Meisa; Mita, Mita; Aini, Nurul; Mandjar, Sherlla Merlinda Laurencia (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Marketing strategy is an aspect that must be owned so that every business, both MSME products and agricultural products, can be optimized. Educational factors and suboptimal application of technology are obstacles that cause a lack of understanding of effective marketing strategies. This article aims to explain how optimizing marketing strategies based on utilitarian value and digital marketing can help UMKM and farmers in Kampung Gambut Siantan Hilir improve the competitiveness of their products, create stronger relationships with consumers, and encourage sustainable local economic growth. Through problem solving methods and data collection techniques through interviews, observations, and documentation studies, the implementation of the PKM program runs smoothly. Kampung Gambut community participation also plays an important role in driving the success of the PKM activities. The result of this activity is to ensure the community's understanding of the importance of optimizing marketing strategies based on utilitarian value and digital marketing. By emphasizing these aspects, UMKM products and agricultural products become more competitive in the market. With the right digital marketing strategy, local products in the Kampung Gambut Siantan Hilir can reach a wider range of consumers, which cannot be reached through traditional marketing methods.